Side-surface openings effects on galloping instability for a rectangular cylinder. Issue 206 (November 2020) - Wang, Jiaqi; Yagi, Tomomi; Ushioda, Jun; Ichikawa, Hidekazu; Yamamoto, Soichiro; Noguchi, Kyohei
Abstract: Discretely distributed side-surface openings have a stabilizing effect on box girders against galloping. This research intends to further investigate the relationship between the size of the openings and galloping instability with respect to aerodynamic response and aerodynamic damping. An additional objective is to explain the stabilization mechanism against galloping owing to the openings. A series of wind tunnel tests was carried out on rectangular cylinders with different-sized openings that were non-dimensionalized as the Opening-area Ratio ( OR ), which is the ratio of the total-openings area to half of the front-surface area. At high wind velocities, increasing the OR from 0 to 0.75 increased the aerodynamic damping, and the separated shear layer gradually approached the model's trailing edge. Increasing it above 0.75 resulted in a decrease of the aerodynamic damping and the separated shear layer reattaching to the model. As OR increased, the galloping onset increased accompanied by the decrease in Strouhal number. Thus, the rectangular cylinder showed good galloping stability owing to the openings, which promoted the reattachment of the separated shear layer on the side surfaces, effectively increasing the body width-to-depth ratio. This research contributes to an innovative method to stabilize rectangular cylinder-like bluff bodies against galloping instability. Highlights: Side-surface openings of the rectangular cylinder stabilize its galloping instability. The galloping onset increases with the opening-area ratio ( OR ). Aerodynamic damping never changes monotonically with OR . Increasing OR promotes reattachment of separated shear layer to upside and downside surfaces. Quasi-steady theory is valid for rectangular cylinder with side-surface openings.